FREQUENCY OF CAUSES OF VENTRICULO-PERITONEAL SHUNT FAILURE IN HYDROCEPHALUS PATIENTS - Ali, Mumtaz; Aman, Raza; Khan, Zahid; Khan, Khalid Mahmood; Siddique, Muhammad; Khanzada, Khalid; Ayub, Shahid; Pervez, Muhammad (Journal of Postgraduate Medical Institute, 2011)
Objective: To analyze ventriculo-peritoneal shunt (VP shunt) failure cases in hydrocephalic patients, in a tertiary care hospital. Methodology: This descriptive study was carried out in the Department of Neurosurgery Lady Reading Hospital Peshawar, from June 2009 to May 2010 (one year).The medical record of all cases operated in last one year was checked from record room. Documentation was done according to proforma designed indicating age, sex, clinical features, investigations with findings on X-rays, CT and MRI and per operative findings. Complications related to upper end, lower end and shunt track were noted. Data was analyzed to assess the causes for shunt failure in hydrocephalus patients. Results: A total of 56 patients were included in this study. There were 43 children and 13 adults. Among children, 26 were males and 17 were females while in adults, 5 were males and 8 were females. Out of these, 28 patients were having blocked shunt, 20 cases with infected shunt, 6 patients had eroded and 2 patients displaced shunt. Conclusion: Although shunt surgery is a common procedure performed for hydrocephalus, different complications were associated in our study where shunt failure was mainly due to shunt dysfunction, infection or breakage of shunt system. Complications were more with upper end. Infection was common in pediatric age group.